Plasmodium falciparum Clonal Population Dynamics during Malaria Treatment - Jafari, Sayeh; Le Bras, Jacques; Bouchaud, Olivier; Durand, Rémy (The Journal of infectious diseases, 2004)
We have developed a new fragment-analysis method to enumerate the clones and to quantify their proportions within Plasmodium falciparum isolates. We prospectively enrolled 20 adult patients with uncomplicated malaria who were returning to France from various sub-Saharan countries, from January 2000 through July 2001. The analysis of clonal populations was performed on blood samples obtained at 10 times: 1 before treatment with oral quinine and 9 during the first 96 h of the treatment. The resistance genotypes pfcrt and dhfr were determined for chloroquine and antifolinics. Multiple P. falciparum genotypes were detected in 19 (95%) of 20 patients: 2, 3, 4, and 5 genotypes were found in 4, 9, 4 and 2 patients, respectively. Disappearance and reappearance of some clones within a few hours was observed. Individual clones represented 0.4%–99.4% of total parasitemia. Surprisingly, in 10 of 15 subjects tested, resistance genotypes varied according to the time of blood collection. These findings may have important implications with regard to the interpretations of resistance studies